Pengembangan Modul Ajar Fisika Kurikulum Merdeka - Sania Ulfa; Asep Irvan Irvani; Resti Warliani (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
This research was conducted to develop the Merdeka Curriculum learning tools, namely the Physics Teaching Module on Alternative Energy material that meets the validity criteria. The research method used is a quantitative method which is interpreted and analyzed qualitatively. The Teaching Module was developed using a 4-D development model which was simplified to 3-D. This Teaching Module was developed based on provisions and characteristics that refer to the learning principles in the Independent Curriculum. Data collection instruments include validation sheets and questionnaires. The validation sheet includes content validation and language validation. Validation was carried out by three experts with expertise in physics education and language education. The questionnaire was given to practitioners, namely two physics subject teachers at one of the high schools in Garut Regency. The data obtained was then processed quantitatively by calculating the percentage of each aspect and the overall percentage. The processing results are then interpreted and analyzed qualitatively to determine product validity. The research results showed that based on the validity test, the Module was declared very valid with a validity percentage of 82.7%. This shows that the module developed is valid and can be used as a learning module.